Perancangan sistem informasi inventory gudang bahan baku dan barang jadi di PT Palapa Engineering Berbasis Web - Junior, Fabio (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2022)
PT Palapa Engineering which is located at Jl. Raya Peusar RT 09/RW 04 Kp. Kadu Kel. Sukamulya District. Cikupa District. Tangerang, the data collection process for raw materials and finished goods is still done manually using ledgers. The data collection process for warehouses for raw materials and finished goods at PT Palapa Engineering is still manual and the data processing process is still less effective. Therefore, the aim of this research is to analyze the current system and design a web-based warehouse inventory information system for raw materials and finished goods. To achieve this goal the author approached the research method, namely field studies, interviews, literature studies and system design using Waterfall and UML (Unified Modeling Language). Application creation using PHP language and database with MySQL. The conclusion is that PT Palapa Engineering's data collection system for raw materials and finished goods is still done manually and there is frequent loss of raw material and finished goods report data, so a new computerized system design is needed, namely with web-based technology.